Modelling silicon etching using inverse methods - Kincanon, Eric (International Journal of Applied Mathematical Research, 2022)
This paper considers a real-world application of a recently presented alternative form of the Gelfand-Levitan equation. Here is considered the case of potential in the plasma above silicon during the etching process. It is shown that although standard methods have significant challenges, the alternative form of the Gelfand-Levitan equation gives a straightforward way to determine the reflection coefficient from an assumed potential.Â Â